Study on Service Quality and Priorities of Pedestrian Path Development in Malioboro Area to Support Sustainable Urban Mobility - Chakam, Muchammad Fuad; Rakhmatulloh, Anita (ASTONJADRO, 2024)
This article aims to study the service quality and prioritize the development of pedestrian paths in the Malioboro area to support sustainable urban mobility. Malioboro is one of the commercial and tourist centers in Yogyakarta city, historically known for its pedestrian-friendly pathways. Challenges such as pedestrian circulation issues, inadequate pedestrian facilities, conflicts between pedestrians and motorized vehicles, and problems with drop-off and stop zones for less organized transportation contribute to the low service quality in the Malioboro area. This study adopts a quantitative approach using direct observation and a questionnaire distributed to 132 pedestrian path users. The collected data is analyzed using descriptive analysis techniques and Importance Performance Analysis (IPA) to understand the existing conditions, quality, and priority of pedestrian path services in the Malioboro area. The study results indicate that the service quality of pedestrian paths in Malioboro faces several challenges. Factors such as motor vehicle traffic density, lack of quality pedestrian infrastructure, and pedestrians’ unsafe behavior contribute to the low service quality. The pedestrian satisfaction analysis using the Customer Satisfaction Index (CSI) revealed a satisfaction rate of 69.19%, categorizing it as "adequate." However, improvements in pedestrian path services are necessary based on the significance of the Malioboro area and its high appeal to pedestrians. The goal is to achieve good or even perfect satisfaction in terms of service quality. An analysis of interests was conducted, resulting in the identification of four quadrants with distinct characteristics. These quadrants serve as a valuable guide for enhancing the quality of pedestrian path services. Quadrant 1 encompasses attributes such as crossing facilities, CCTV surveillance, protection from weather conditions (rain, heat, cold), and parking convenience. Despite their high importance, these variables received low satisfaction ratings from respondents. Enhancing both the quantity and quality of these variables is crucial. Policymakers should pay special attention to these four variables and implement concrete measures to surpass the "adequate" assessment and attain better pedestrian service satisfaction. By implementing these measures, it is expected that Malioboro can serve as an example in supporting sustainable urban mobility by providing good and safe services for pedestrians. This study can also provide guidance and input for the government and relevant stakeholders in decision-making regarding pedestrian path infrastructure development in similar areas.